Study the Influence of Mixing Thethods and Leather Fiber Content on Properties of Epoxy Composite - Bui, Van Huan; Nguyen, Pham Duy Linh; Nguyen, Thi Duyen (Old Journal, 2019)
Leather is a traditional material for making shoes and leather products, so in Vietnam, every year, large amounts of chrome tanned leather wastes are generated. In this study, the dry leather waste was grounded in a hammer miller, to get short leather fibers with a diameter of 0.08 ± 0.3 mm, length 5 ÷ 15 mm. Fibers are mixed with epoxy resin added additives by traditional mixing method, resin pre-mixing that called masterbatch, dilution into mold by RTM. Composite samples were tested for breaking strength, bending strength, impact strength and water absorption. The morphology of the composite material was observed by scanning electron microscope SEM. The results show that the master batch mixing method gives good results, suitable for mixing leather fibers with epoxy resin. With this method of mixing, the epoxy resin composite with leather fiber content of 40% obtains good mechanical properties, maximum water absorption 6.2%, as well as, the best disperses phases in material.